Antiacne and anti dandruff potential of gamma Peptide isolated from clariasgariepinusmucus - BRINDHA DURAIRAJ,; SANTHI. R,; RENI. S, (International Journal of Pharma and Bio Sciences, 2018)
Fish antimicrobial peptides are recognized as a component of the host’s defence against infection. The present study was undertaken to isolate the gamma peptides from the epidermal mucus of Clariasgariepinus. The isolated gamma peptides were tested against five pathogenic bacteria and it is mainly concentrated on the acne causing microorganism and dandruff causing fungi. The results of the present investigation revealed that the isolated gamma peptide from the mucus of the Clarias gariepinus having remarkable antimicrobial activity. SDS–PAGE of fish mucus showed many protein bands with molecular size ranging from 20 to 100KDa and only one clear band in the mucus was detected in the gel that represented size of 35kDa.